Techno-economic assessment of radial turbomachinery in process gas applications - Albusaidi, Waleed (Cranfield University, 2016)
This research aims to assess the causes of inefficient and unstable operation of centrifugal compressors and turboexpanders in process gas applications in order to provide a solution for performance restoration and enhancement. It encompasses thermodynamic and flow evaluations to examine the efficiency and operating range improvement options of new units. Besides, this work is complemented by a technoeconomic analysis to provide a rounded outcome from these studies. In order to achieve the desired objectives, a novel integrated approach has been developed to assess the design and performance of multi-stage centrifugal compressors. The proposed systematic methodology involves five basic elements including evaluation of compressor selection, compressor sizing and casing structure, performance prediction at the design and off-design conditions, modelling of efficiency and head deterioration causes; and stage design evaluation. This will contribute towards evaluating the geometrical parameters of the new units’ designs at the early preliminary design phase, and thus, will be useful to identify the options for efficiency and operating range enhancements. For installed units, this approach can be implemented to assess the cause of inefficient and unstable operation by assessing the available operation data. A method was developed to predict the performance curve of multi-stage centrifugal compressor based on a stage stacking technique. This approach considers the advantages of Lüdtke and Casey-Robinson methods with an incorporation of a methodology for compressor selection and sizing to generate more accurate results. To emphasize the validity of the developed model, it has been evaluated for both low and high flow coefficient applications. The obtained results show a significant improvement in the estimated efficiency, pressure ratio, shaft power and operating range as compared with the existing methods. The centrifugal compressor is designed to run under various operating conditions and different gas compositions with the primary objective of high efficiency and reliability. Therefore, a new iterative method has been developed to predict the equivalent compressor performance at off-design conditions. This technique uses the performance parameters at design conditions as a reference point to derive the corresponding performance characteristics at numerous suction conditions with less dependency on the geometrical features. Through a case study on a gas transport centrifugal compressor, it was found that the developed approach can be applied for design evaluation on the expected variation of working conditions, and for the operation diagnosis of installed units as well. Furthermore, a parametric study has been conducted to investigate the effect of gas properties on the stage efficiency, surge margin, and compressor structure. The obtained results support the need for considering the gas properties variation when the off-design performance is derived. To evaluate the impact of internal blockage on the performance parameters, this study proposed an approach to model the effect of non-reactive deposits, which has been qualified using four operation cases and the obtained results are compared with the internal inspection findings from the stage overhauling process. This also covers the influential aspects of flow blockage on the technical and economic values. Since the main challenge here is to analyze the process gas composition in real time, the influences of the non-reactive deposits have been compared with the effect of the unanticipated gas composition change. Subsequently, it has turned out that the pressureratio parameter is not enough to assess the possibility of flow blockage and unexpected gas properties change. Moreover, it was observed that the stage discharge pressure was more sensitive to the fouled aftercooler comparing with suction and internal blockage. However, the effect of contaminated aftercooler on the surge point and discharge pressure and temperature of the upstream stage was found greater than its impact on the shaft power. Thus, a substantial surge margin reduction was detected when the first stage was operating with a fouled aftercooler comparing with the measured reduction as a result of unanticipated gas properties change. Furthermore, a larger pressure ratio drop was measured in the case of liquid carryover which revealed a more significant impact of the two phases densities difference comparing with the gas volume fraction (GVF) effect. The possibility of hydrate formation has been assessed using hydrate formation temperature (HFT) criteria. Additionally, this research highlights a number of challenges facing the selection of typical centrifugal stage design by assessing the contribution of design characteristics on the operating efficiency and stable flow range. Besides, an empirical-based-model was established to select the optimum impeller and diffuser configurations in order to make a compromise decision based on technical and economic perspective. It was concluded that there is no absolute answer to the question of optimum rotor and stator configuration. The preliminary aerothermodynamic evaluation exposed that the selection of the optimum impeller structure is governed by several variables: stage efficiency, pressure loss coefficient, manufacturing cost, required power cost, resonance frequency and stable operating range. Hence, an evaluation is required to compromise between these parameters to ensure better performance. Furthermore, it was argued throughout this study that the decision-making process of the typical stage geometrical features has to be based upon the long-term economic performance optimization. Thus, for higher long-term economic performance, it is not sufficient to select the characteristics of the impeller and diffuser geometry based on the low manufacturing cost or efficiency improvement criterion only. For turboexpanders, a simple and low cost tool has been developed to determine the optimum turboexpander characteristics by analysing the generated design alternatives. This approach was used in designing a turboexpander for hydrocarbon liquefaction process. Moreover, since the turboexpanders are expected to run continuously at severe gas conditions, the performance of the selected turboexpander was evaluated at different inlet flow rates and gas temperatures. It has turned out that designing a turboexpander with the maximum isentropic efficiency is not always possible due to the limitations of the aerodynamic parameters for each component. Therefore, it is necessary to assess the stage geometrical features prior the construction process to compromise between the high capital cost and the high energetic efficiency.
Keywords: Centrifugal compressor; Turboexpander; Efficiency; Operating range; Design conditions; Off-design; Deterioration; Flow blockage; Design evaluation; Operation diagnosis; Geometrical parameters; Gas compositions